How Computers Have Changed the Wage Structure: Evidence from Microdata, 1984-1989 - Krueger, A. B. (Quarterly Journal of Economics, 1993)
This paper uses Current Population Survey data to examine whether workers who use a computer at work earn a higher wage rate than otherwise similar workers who do not use a computer at work. A variety of models are estimated to try to correct for unobserved variables that might be correlated with job-related computer use and earnings. Estimates suggest that workers who use computers on their job earn 10 to 15 percent higher wages. Additionally, the expansion in computer use in the 1980s can account for one-third to one-half of the increase in the rate of return to education.